Orbital Shapes of Asteroids in Cometary Orbits based on 0.7m Telescope Imaging - S. Dueantakhu (2018)
© Published under licence by IOP Publishing Ltd. The study of orbital elements of Asteroids in Cometary Orbits (ACOs) is based on images taken by a 0.7-m telescope to find positions of asteroids and calculate their orbital elements. This work focuses on variation of positions and orbital shape of an asteroid, 1667Pels, which is obtained by analyzing orbital elements and minimum orbital intersection distances. Each observation, those parameters are affected by the gravity from Jupiter on ACOs. The accuracy of single site data was calibrated by comparing the result from this work to other observations in Minor Planet Center database.